Pardon me! - Miyares, Daniel (Simon & Schuster Books for Young Readers, 2014)
A bird tries to keep his spot to himself only to discover that spot is not so safe
Keywords: Birds; Animals; Sharing; Humorous stories; Vögel; Teilen; Tiere; Bilderbuch